The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1042/bj2810709
|View full text |Cite
|
Sign up to set email alerts
|

Global ischaemia induces a biphasic response of the mitochondrial respiratory chain. Anoxic pre-perfusion protects against ischaemic damage

Abstract: Studies of Langendorff-perfused rat hearts have revealed a biphasic response of the mitochondrial respiratory chain to global ischaemia. The initial effect is a 30-40% increase in the rate of glutamate/malate oxidation after 10 min of ischaemia, owing to an increase in the capacity for NADH oxidation. This effect is followed by a progressive decrease in these oxidative activities as the ischaemia is prolonged, apparently owing to damage to Complex I at a site subsequent to the NADH dehydrogenase component. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 33 publications
8
91
1
Order By: Relevance
“…Complex 1 and 5 have been identified as the two more fragile mitochondrial respiratrypan blue exclusion test. Taken together, our results indicate that LDH and MTT tests do not adequately astory chain complexes (11,19,31,32,43). Indeed, the activity of complex 1 is rapidly altered following cold issess viability and that intracellular ATP concentration is probably the most sensitive parameter to detect early chemia of whole organs (19,31), by a still unknown mechanism.…”
Section: Activation Dna Fragmentation and Apoptosismentioning
confidence: 91%
“…Complex 1 and 5 have been identified as the two more fragile mitochondrial respiratrypan blue exclusion test. Taken together, our results indicate that LDH and MTT tests do not adequately astory chain complexes (11,19,31,32,43). Indeed, the activity of complex 1 is rapidly altered following cold issess viability and that intracellular ATP concentration is probably the most sensitive parameter to detect early chemia of whole organs (19,31), by a still unknown mechanism.…”
Section: Activation Dna Fragmentation and Apoptosismentioning
confidence: 91%
“…Oxidative phosphorylation is inhibited during hypoxia and deteriorates upon reoxygenation. 27,40 The progressive deterioration of mitochondrial function during reperfusion may result from MPT triggered by the normalization of intracellular pH and burst of ROS activity. 41 Opening of the MPT pore would cause immediate collapse of the mitochondrial membrane potential and inhibits ATP synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of trimetazidine was attributed by the authors not to its antioxidant properties, but to changes in lipid metabolism (Fantini et al, 1994). In other models of ischemia-reperfusion, it has been demonstrated that the impact of ischemia on the mitochondrial respiratory chain mainly occurs at the level of complex I (Veitch et al, 1992).…”
Section: Introductionmentioning
confidence: 99%